RESEARCH ON ENVIRONMENTAL STANDARDS FOR THE STORAGE OF PRECIOUS CULTURAL RELICS - Fan Yu Jian, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Precious cultural relics are important carriers of human civilization and historical memory. Their preservation and storage are essential tasks for museums, archives, and cultural heritage institutions worldwide. Environmental conditions such as temperature, humidity, light, air quality, and biological factors directly influence the physical and chemical stability of cultural relics. Improper storage environments may accelerate deterioration, corrosion, fading, cracking, and biological damage. Therefore, establishing scientific environmental standards for the storage of precious cultural relics has become a major concern in the field of cultural heritage protection. This paper analyzes the importance of storage environment standards, discusses the main environmental factors affecting relic preservation, examines international standards and modern technologies used in museum storage systems, and proposes suggestions for improving cultural relic storage management. The study aims to provide theoretical references for the sustainable preservation of precious cultural heritage.